2000
DOI: 10.1007/s004250000365
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll is not the primary photoreceptor for the stimulation of P-type H + pump and growth in variegated leaves of Coleus × hybridus

Abstract: There has been persisting controversy over the role of photosynthesis in the stimulation of the plasma membrane H+-ATPase and growth of dicotyledonous leaves by light. To investigate this, we compared the effects of light on growth, H+ net efflux and membrane potential (Vm) of strips which contained either only chlorophyll-free (white) mesophyll cells or chlorophyll-containing (green) cells cut from variegated Coleus leaves. White mesophyll cells responded to white, blue and red light with a hyperpolarization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Light-induced growth of the mutant was ϳ50% of that observed in wild type plants (data not shown). Despite impaired photosynthesis and slower growth, the light-grown OsCHLH rice mutant seedlings were well developed with fully expanded leaves, indicating that growth can occur in the absence of photosynthesis (20,30). It is likely that the cytochrome and its branched alternative respiratory pathways in mitochondria coordinately balance ubiquinone pool oxidation/reduction and carbon skeleton turnover in response to cytosolic ATP levels (60).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Light-induced growth of the mutant was ϳ50% of that observed in wild type plants (data not shown). Despite impaired photosynthesis and slower growth, the light-grown OsCHLH rice mutant seedlings were well developed with fully expanded leaves, indicating that growth can occur in the absence of photosynthesis (20,30). It is likely that the cytochrome and its branched alternative respiratory pathways in mitochondria coordinately balance ubiquinone pool oxidation/reduction and carbon skeleton turnover in response to cytosolic ATP levels (60).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies showed that light-induced membrane hyperpolarization is modulated by photosynthesis-dependent plasma membrane H ϩ -ATPases in mesophyll cells (27,29). However, this hyperpolarization clearly occurred in response to light absorption by pigments other than chlorophyll, demonstrating that chlorophyll-deficient cells also exhibit light-induced membrane hyperpolarization (30), which differs from the findings of the earlier study (16). Taken together, the data suggest that lightdriven photosynthesis is not directly involved in the activation of K out channel current in the plasma membrane, although the possibility of direct K ϩ transport by other ATPases (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With V m values around -200 mV, mesophyll cells from sunflower leaves are much more polarized than in leaves of other higher land plants. [29][30][31] Both leaf and epicotyl strips were isolated from growing organs having reached about 50% of their final size. Inserting microelectrodes we wanted to establish whether spikes could be recorded in the cells of isolated epicotyl and leaf strips.…”
Section: Seedsmentioning
confidence: 99%
“…Leaf optical properties may contribute to diminution of GFP fluorescence Absorption spectra for green and white segments of variegated Coleus hybridus leaves (Stahlberg et al, 2000) reveal substantial absorption in green regions at the excitation (488 nm) and emission (509 nm) wavelengths of GFP. This implies that observation of GFP fluorescence in leaves can be hindered by both absorption of the excitation light (thus diminishing the excitation intensity) and reabsorption of the emitted green signal.…”
Section: How Arabidopsis Hides Its Dark Sidementioning
confidence: 99%